PENGARUH PENGGUNAAN MULTIMEDIA PEMBELAJARAN BERBASIS WORDWALL TERHADAP MOTIVASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SDN 1 GARAWANGI - Lismiyati; Agus Saeful Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: (1) Determine students’ learning motivation before and afterusing Wordwall-based learning multimedia in the Pancasila Education subject forfifth-grade students at SDN 1 Garawangi. (2) Examine whether the use ofWordwall-based learning multimedia affects students’ learning motivation in thePancasila Education subject for fifth-grade students at SDN 1 Garawangi. Thisresearch uses a quantitative approach. The research design applied is a Quasi-Experimental Non-Equivalent Control Group Design. This type of design aims totest a causal relationship between a treatment (intervention) given to a certaingroup by comparing it to another group that does not receive any treatment. In thisstudy, the population consisted of all fifth-grade students at SDN 1 Garawangi,while the sample included 23 students in class Va (control group) and 26 studentsin class Vb (experimental group). The average posttest score in the control class(Va) was 85.7, and the average score in the experimental class (Vb) was 91.4,showing an increase of 6.76%. Based on the Independent Sample T-Test resultsin the table above, the significance value in Levene’s Test was 0.157 > 0.05,indicating that the data had equal variances (equal variances assumed). In the t-test for Equality of Means section, the significance value (Sig. 2-tailed) was 0.001< 0.05, and the t-value was -3.494, which means there was a significant differencebetween the control and experimental groups. Therefore, it can be concluded thatthe use of Wordwall-based learning multimedia applied in the experimental groupsignificantly influenced student learning outcomes compared to the control group.